2013
DOI: 10.1093/czoolo/59.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in feeding preferences and ranging patterns in spider monkeys Ateles geoffroyi yucatanensis of northeastern Yucatan peninsula, Mexico

Abstract: The spider monkey, a fruit specialist and important seed dispersal agent in the Neotropics, is an endangered primate due to habitat loss, hunting and the pet trade. Spider monkeys have been the subject of a few studies in Central and South America, but little is known about the diet and ranging for this primate in southern Mexico. Here we report the results of a six-month long study (October 2010 to March 2011) of the feeding preferences and ranging patterns of the Yucatan spider monkey Ateles geoffroyi yucata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(40 reference statements)
1
3
0
2
Order By: Relevance
“…This preference has been reported for other Mexican southeastern populations of Ateles (Martínez and GalindoLeal, 2002;Ramos-Fernández and Ayala-Orozco, 2002;González-Zamora et al, 2009;Scherbaum and Estrada, 2013) in common and dominant plant families in tropical forests such as Fabaceae and Moraceae (Primack and Corlett, 2005). The diet of Ateles is mainly based on fleshy fruits and a variable proportion of leaves and blossoms (García-Orduña, 2003).…”
Section: Seed Handlingsupporting
confidence: 72%
“…This preference has been reported for other Mexican southeastern populations of Ateles (Martínez and GalindoLeal, 2002;Ramos-Fernández and Ayala-Orozco, 2002;González-Zamora et al, 2009;Scherbaum and Estrada, 2013) in common and dominant plant families in tropical forests such as Fabaceae and Moraceae (Primack and Corlett, 2005). The diet of Ateles is mainly based on fleshy fruits and a variable proportion of leaves and blossoms (García-Orduña, 2003).…”
Section: Seed Handlingsupporting
confidence: 72%
“…We used remote camera traps both at ground-level and in the canopy, and used baited pitfall traps, to highlight the ecological impacts of spider monkey sleeping sites and their associated latrines. In summary: (1) Arboreal cameras allowed us to characterize spider monkey sleeping site use and composition; (2) terrestrial cameras allowed us to confirm that latrines attract greater vertebrate visitation rates, some of which are important secondary seed dispersing species; (3) baited pitfall traps indicate that latrines associated with sleeping sites attract a greater abundance and biomass of secondary seed-dispersing dung beetles that shape brown food webs; (4) floristic analysis of latrines and direct observations determined a total of 111 plant species consumed by spider monkeys (over half of these were detected by assessment of the 10 surveyed latrines; easier and less labor-intensive than direct observations (e.g., Scherbaum and Estrada [49] observed only 42 species of plants consumed in 6 months of field work)); and (5) chemical analysis of soils showed that latrines create heterogeneity in the potassium and manganese levels of rainforest soils. We believe this work highlights that the high fidelity of spider monkeys to sleeping sites leads to a hotspot of ecological interaction and activity which may have substantial downstream impacts on rainforest floristic composition and maintenance of diversity.…”
Section: Discussionmentioning
confidence: 99%
“…BG is the botanical garden of Puerto Morelos, Quintana Roo (20° 51' N, 86° 53' W). The majority of the 65-hectare area consists of medium semi-deciduous forest and mangrove (Scherbaum and Estrada 2013). Spider monkeys are habituated to human presence as BG receives visitors on a daily basis, and several research projects have been carried out on them (e.g., Scherbaum and Estrada 2013).…”
Section: Study Areas and Subjectsmentioning
confidence: 99%